2014
DOI: 10.9715/kila.2014.42.3.035
|View full text |Cite
|
Sign up to set email alerts
|

The Faunae before and after Creating the Solbangjuk Wetland Ecological Park Located in Jecheon-City were Compared

Abstract: In this study, the faunae before and after creating the Solbangjuk Wetland Ecological Park located in Jecheon-city were compared. As a result, the change of the fauna according to the creation of the park showed the phenomenon that the species having the strong wilderness are reduced and the rate of general species become higher. In addition, the species which receive the restrictions for moving such as mammals, amphibians and reptiles are being gradually decreased by the increased visitors owing to the creati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
1
0
1
Order By: Relevance
“…다양한 동식물의 서식과 이동을 가 능하게 하는 비오톱은 도시생태계를 개선하는 데 중요한 역할을 하는 것으로 알려져 있다 (Lee and Jang, 2000). 독 일이나 일본과 같은 선진국의 경우 20 ~ 30년 전부터 비 오톱의 생태적 가치와 기능에 관한 연구를 수행해 왔으며 우리나라 또한 1995년부터 비오톱 개념의 본격적인 도입 을 시작으로 (Lee, 1996), 최근에는 멸종위기 종의 서식지 나 생물 종다양성 증가 등을 위한 공원 내 연못이나 습지 조성에 관한 연구가 활성화되고 있다 (Byeon, 2010;Kim et al, 2014). (Day, 1983;Langhans and Tockner, 2006;Lee and Kim, 2014;Neckles and Neill, 1994) (Howard and Howard, 1974;Lee and Kim, 2014).…”
Section: 이보은・전영준・장유림・김재근 한국습지학회 제17권 제2호 2015unclassified
“…다양한 동식물의 서식과 이동을 가 능하게 하는 비오톱은 도시생태계를 개선하는 데 중요한 역할을 하는 것으로 알려져 있다 (Lee and Jang, 2000). 독 일이나 일본과 같은 선진국의 경우 20 ~ 30년 전부터 비 오톱의 생태적 가치와 기능에 관한 연구를 수행해 왔으며 우리나라 또한 1995년부터 비오톱 개념의 본격적인 도입 을 시작으로 (Lee, 1996), 최근에는 멸종위기 종의 서식지 나 생물 종다양성 증가 등을 위한 공원 내 연못이나 습지 조성에 관한 연구가 활성화되고 있다 (Byeon, 2010;Kim et al, 2014). (Day, 1983;Langhans and Tockner, 2006;Lee and Kim, 2014;Neckles and Neill, 1994) (Howard and Howard, 1974;Lee and Kim, 2014).…”
Section: 이보은・전영준・장유림・김재근 한국습지학회 제17권 제2호 2015unclassified
“…The factors affecting the changes in butterfly communities are explained in relation to changes in habitat environments, changes in surrounding landscape, and changes in climate (Debinski et al 2006;Kim et al 2014). It was found that species with local distribution were eventually extinguished in population studies on environmental changes in habitats (Kim et al 1999), although some species that inhabited disturbed areas widened the distribution range with the expanded dispersal of the population (Park et al 2014).…”
Section: Introductionmentioning
confidence: 99%